The Bermuda Triangle : opposing viewpoints - Gaffron, Norma, 1931- (St. Paul, Minn. : Greenhaven Press, 1988)
Explores the mysteries surrounding the disappearances of planes and ships in the Bermuda Triangle.
Includes index.
Bibliography: p. 91.
Keywords: Bermuda Triangle -- Juvenile literature; Bermuda Triangle